2012
DOI: 10.1021/mp200162b
|View full text |Cite
|
Sign up to set email alerts
|

Provisional Biopharmaceutical Classification of Some Common Herbs Used in Western Medicine

Abstract: The aim of this study was to classify some markers of common herbs used in Western medicine according to the Biopharmaceutical Classification System (BCS). The BCS is a scientific approach to classify drug substances based upon their intestinal permeability and their solubility, at the highest single dose used, within the physiologically relevant pH ranges. Known marker components of twelve herbs were chosen from the USP Dietary Supplement Compendium Monographs. Different BCS parameters such as intestinal perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 11 publications
2
39
0
1
Order By: Relevance
“…For genistein, a high clogP value leads to low aqueous solubility and poor dissolution profile, which may reduce the proportion of genistein contacting enterocytes (Lennernäs, 2007). Previous reports revealed an aqueous solubility of genistein of only about 10 µM (Waldmann et al, 2012), and in this study, we found a low dissolution rate in simulated aqueous gastrointestinal fluids (Fig. 3B).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…For genistein, a high clogP value leads to low aqueous solubility and poor dissolution profile, which may reduce the proportion of genistein contacting enterocytes (Lennernäs, 2007). Previous reports revealed an aqueous solubility of genistein of only about 10 µM (Waldmann et al, 2012), and in this study, we found a low dissolution rate in simulated aqueous gastrointestinal fluids (Fig. 3B).…”
Section: Discussionsupporting
confidence: 56%
“…Waldmann et al reported that genistein has water solubility of 11.65 µg/mL at neutral pH (Waldmann et al, 2012), so the aqueous solubility of genistein is much less than the "highest dose strength" of 30 mg fully dissolved in 250 mL water. We evaluated solubility with excess G7P dissolved in a small amount of deionized water at 37°C.…”
Section: Chemical Properties Of G7p and Its Stability In Sgf And Sifmentioning
confidence: 99%
See 1 more Smart Citation
“…Silymarin, a flavonoid complex extracted from milk thistle plant Silybum marianum, has been widely used for centuries in the therapy of liver diseases and a host of other diseases (Pade and Stavchansky, 2008;Waldmann et al, 2012). Silybin is one of the major and pharmacologically active compounds in silymarin and has been developed and marketed as a drug in China for the therapy of liver diseases (Fong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, to quantify herbal markers dissolved in buffer media, herbal residues have to be tested for the presence of analytical markers to ensure saturation solubility is reached. Another approach to determine provisionally the pH dependent solubility of analytical herbal markers was reported by Lang et.al (12). The software program ADMET Predictor was used to estimate biopharmaceutically relevant descriptors such as solubility.…”
Section: Solubility Determinationmentioning
confidence: 99%